Rapid volume pulsation of the extracellular space coincides with epileptiform activity in mice and depends on the NBCe1 transporter. (29th May 2021) - Colbourn, Robert; Hrabe, Jan; Nicholson, Charles; Perkins, Matthew; Goodman, Jeffrey H.; Hrabetova, Sabina
Abstract : Key points: Extracellular space (ECS) rapid volume pulsation (RVP) accompanying epileptiform activity is described for the first time. Such RVP occurs robustly in several in vitro and in vivo mouse models of epileptiform activity. In the in vitro 4‐aminopyridine model of epileptiform activity, RVP depends on the activity of the electrogenic Na + /HCO3 – cotransporter (NBCe1). NBCe1 pharmacological inhibition suppresses RVP and epileptiform activity. Inhibition of changes in ECS volume may be a useful target in epilepsy patients who are resistant to current treatments. ​ Abstract: The extracellular space (ECS) of the brain shrinks persistently by approximately 35% during epileptic seizures. Here we report the discovery of rapid volume pulsation (RVP), further transient drops in ECS volume which accompany events of epileptiform activity. These transient ECS contractions were observed in multiple mouse models of epileptiform activity both in vivo (bicuculline methiodide model) and in vitro (hyaluronan synthase 3 knock‐out, picrotoxin, bicuculline and 4‐aminopyridine models). By using the probe transients quantification (PTQ) method we show that individual pulses of RVP shrank the ECS by almost 15% in vivo . In the 4‐aminopyridine in vitro model, the individual pulses of RVP shrank the ECS by more than 4%, and these transient changes were superimposed on a persistent ECS shrinkage of 36% measured with the real‐time iontophoretic method. In this in vitro model, we investigated several channels and transporters that may be required for the generation of RVP and epileptiform activity. Pharmacological blockages of Na + /K + /2Cl – cotransporter type 1 (NKCC1), K + /Cl – cotransporter (KCC2), the water channel aquaporin‐4 (AQP4) and inwardly rectifying potassium channel 4.1 (Kir4.1) were ineffective in halting the RVP and the epileptiform activity. In contrast, pharmacological blockade of the electrogenic Na + /HCO3 – cotransporter (NBCe1) by 4, 4'‐diisothiocyano‐2, 2'‐stilbenedisulfonic acid (DIDS) eliminated both the RVP and the persistent ECS shrinkage. Importantly, this blocker also stopped the epileptiform activity. These results demonstrate that RVP is closely associated with epileptiform activity across several models of epileptiform activity and therefore the underlying mechanism could potentially represent a novel target for epilepsy management and treatment. Key points: Extracellular space (ECS) rapid volume pulsation (RVP) accompanying epileptiform activity is described for the first time. Such RVP occurs robustly in several in vitro and in vivo mouse models of epileptiform activity. In the in vitro 4‐aminopyridine model of epileptiform activity, RVP depends on the activity of the electrogenic Na + /HCO3 – cotransporter (NBCe1). NBCe1 pharmacological inhibition suppresses RVP and epileptiform activity. Inhibition of changes in ECS volume may be a useful target in epilepsy patients who are resistant to current treatments. ​